2018
DOI: 10.1016/j.kint.2017.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow reserve is predictive of the risk of cardiovascular death regardless of chronic kidney disease stage

Abstract: Microvascular rarefaction is found in experimental uremia, but data from patients with chronic kidney disease (CKD) are limited. We therefore quantified absolute myocardial blood flow and coronary flow reserve (the ratio of peak to resting flow) from myocardial perfusion positron emission tomography scans at a single institution. Individuals were classified into standard CKD categories based on the estimated glomerular filtration rate. Associations of coronary flow reserve with CKD stage and cardiovascular mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 46 publications
(52 reference statements)
4
66
0
Order By: Relevance
“…A hospital-based prospective study with 3,946 participants in the United States found that there was an inverse relationship between CKD stage and coronary flow reverse using positron emission tomography. 37 Uremia may lead to endothelial cell dropout or may cause angiogenesis to fail to occur as a compensatory response to ischemia, possibly because of destabilized hypoxia-inducible factor or the inhibition of nitric oxide synthase by asymmetric dimethylarginine. 38,39 In another pathway, elevated levels of asymmetric dimethyl arginine and other inhibitors of angiogenesis may lead to myocardial fibrosis and capillary rarefaction through endothelial-to-mesenchymal transformation; that is, the transformation of endothelial cells into fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…A hospital-based prospective study with 3,946 participants in the United States found that there was an inverse relationship between CKD stage and coronary flow reverse using positron emission tomography. 37 Uremia may lead to endothelial cell dropout or may cause angiogenesis to fail to occur as a compensatory response to ischemia, possibly because of destabilized hypoxia-inducible factor or the inhibition of nitric oxide synthase by asymmetric dimethylarginine. 38,39 In another pathway, elevated levels of asymmetric dimethyl arginine and other inhibitors of angiogenesis may lead to myocardial fibrosis and capillary rarefaction through endothelial-to-mesenchymal transformation; that is, the transformation of endothelial cells into fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…CFR may be impaired in patients with significant stenoses of the epicardial coronary arteries, but also patients with microvascular dysfunction suggesting a decreased functional capacity of the microcirculation to adapt to the myocardium needs . Impaired CFR has been demonstrated in various populations at increased cardiovascular risk including patients with CKD and dialysis patients and carries significant both diagnostic (coronary artery disease) and prognostic value . A cutoff value of CFR >2.0 has been considered normal and associated with increased survival rates .…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic acquisition scan of 4 min 40 s was performed with corresponding frame times of (14 × 5 s, 3 × 10 s, 3 × 20 s, and 4 × 30 s). After a 10-min decay of the [ 15 Adenosine was initiated 2 min before the stress scan for maximal vasodilatation. The mean radiation dose was 1 mSv for the perfusion study.…”
Section: Myocardial Petmentioning
confidence: 99%
“…Decreased MPR has been also documented in several preatherosclerotic states like hypertension [10] and dyslipidemia [11] without obstructive CAD. Furthermore, reduced MPR has been established in patients with mild to severe CKD [12][13][14], and it is associated with CV mortality also in patients with CKD [15,16].…”
Section: Introductionmentioning
confidence: 99%